The Alteration of Salivary Immunoglobulin A in Autism Spectrum Disorders - Gong, Wuyi; Qiao, Yanan; Li, Bosheng; Zheng, Xiaoguo; Xu, Ruihuan; Wang, Mingbang; Mi, Xiaohui; Li, Yongming (Frontiers in Psychiatry, 2021)
Objectives: Autism spectrum disorders (ASD) are neurodevelopmental disorders with changes in the gut and oral microbiota. Based on the intimate relationship between the oral microbiota and oral mucosal immunity, this study aimed to investigate changes in salivary immunoglobulin A (IgA) level in ASD and the underlying mechanism for any such changes. Methods: We recruited 36 children diagnosed with ASD and 35 normally developing children and measured their salivary IgA content using enzyme-linked immunosorbent assay (ELISA). The valproate (VPA) -treated ASD mouse model was established by prenatal exposure to valproate and mouse salivary IgA content was also quantified by ELISA. The submandibular glands of VPA and control mice were isolated and analyzed using qRT-PCR, immunofluorescence staining, and flow cytometry. ASD-related Streptococci were co-incubated with the human salivary gland (HSG) cell line, and western blotting was used to detect the levels of relevant proteins. Results: We found that salivary IgA content was significantly decreased in patients with ASD and had a significant ASD diagnostic value. The salivary IgA content also decreased in VPA mice and was significantly correlated with autistic-like behaviors among them. The mRNA and protein levels of the polymeric immunoglobulin receptor (Pigr) were downregulated in the submandibular glands of VPA mice and the Pigr mRNA level was positively correlated with mouse salivary IgA content. HSG cells treated with ASD-related Streptococci had reduced PIGR protein level. Conclusion: Therefore, protective IgA levels were reduced in the saliva of individuals with ASD, which correlated with the bacteria-induced downregulation of Pigr in salivary glands. This study suggests a new direction for ASD diagnosis and prevention of oral diseases in ASD cohorts and provides evidence for the ASD mucosal immunophenotype in the oral cavity.